Deep Learning as a Pedagogical Paradigm for Arabic Grammar Learning: A Critical Conceptual Review - Asmaniah, Neli; Habsi, Syifa Pauzia; Singgar Mantahari Dalimunthe (Indonesian Journal of Arabic Education and Learning, 2026)
The transformation of Indonesia’s education curriculum in the digital era and the Industrial Revolution 5.0 requires Arabic language instruction particularly grammatical studies to shift toward a deeper and more meaningful learning approach at the senior secondary school level. This study aims to analyze the implementation of a deep learning approach in Arabic grammar instruction based on conceptual analysis and recent scholarly literature. The research adopts a qualitative descriptive approach using a literature review method, conducted through stages of identifying, selecting, and analyzing relevant sources drawn from academic books and peer-reviewed journal articles. The findings indicate that the deep learning approach in Arabic grammar instruction is grounded in in-depth conceptual understanding, the interconnectedness of linguistic structures, and the application of authentic learning contexts. Its implementation is supported by digital technology-based learning strategies, collaboration, problem-solving activities, and continuous evaluation. These conceptual findings affirm that the deep learning approach not only enhances the effectiveness of Arabic grammar learning but also contributes to the development of students’ higher-order thinking skills, including critical, creative, collaborative, and communicative abilities. Therefore, this approach is considered a relevant pedagogical alternative for Arabic grammar instruction in the era of modern education.